Secret Affairs: Britain’s Collusion with Radical Islam By Mark Curtis (London: Serpent’s Tail, 2010. pbk. 423 pages.) (American Journal of Islam and Society, 2012)
This book deals with the old-new issue pertaining to the dialectics of Western,particularly the British“Islamists” collusion during the decades of thetwentieth century and into the twenty-first century. The issue is old becausemuch of such collaboration has been either known or suspected, especiallyduring the era of the visible rise of threatening communist ideology sincethe Russian Revolution of 1917, as well as other socialist ideas. It is newbecause of the twists it has taken in the context of the sudden disappearanceof the common Soviet ideological enemy, which had glued both partiesto each other—and the ensuing so-called war on global terrorism. Theissue is also dialectical as it pertains to the seeming love-hate relationshipthat permeated Western-Islamist interaction, and which despite all soundingsof mutual vituperations and appearances of alleged resentment, neverreally stood in the way of both finding reasons and ways for colluding ...